Synergistic Effect of Caffeine and Glucocorticoids on Expression of Surfactant Protein B (SP-B) mRNA - Fehrholz, Markus (Public Library of Science, 2012)
Administration of glucocorticoids and caffeine is a common therapeutic intervention in the neonatal period, but possible interactions between these substances are still unclear. The present study investigated the effect of caffeine and different glucocorticoids on expression of surfactant protein (SP)-B, crucial for the physiological function of pulmonary surfactant. We measured expression levels of SP-B, various SP-B transcription factors including erythroblastic leukemia viral oncogene homolog 4 (ErbB4) and thyroid transcription factor-1 (TTF-1), as well as the glucocorticoid receptor (GR) after administering different doses of glucocorticoids, caffeine, cAMP, or the phosphodiesterase-4 inhibitor rolipram in the human airway epithelial cell line NCI-H441. Administration of dexamethasone (1 µM) or caffeine (5 mM) stimulated SP-B mRNA expression with a maximal of 38.8±11.1-fold and 5.2±1.4-fold increase, respectively. Synergistic induction was achieved after co-administration of dexamethasone (1 mM) in combination with caffeine (10 mM) (206±59.7-fold increase, p<0.0001) or cAMP (1 mM) (213±111-fold increase, p = 0.0108). SP-B mRNA was synergistically induced also by administration of caffeine with hydrocortisone (87.9±39.0), prednisolone (154±66.8), and betamethasone (123±6.4). Rolipram also induced SP-B mRNA (64.9±21.0-fold increase). We detected a higher expression of ErbB4 and GR mRNA (7.0- and 1.7-fold increase, respectively), whereas TTF-1, Jun B, c-Jun, SP1, SP3, and HNF-3α mRNA expression was predominantly unchanged. In accordance with mRNA data, mature SP-B was induced significantly by dexamethasone with caffeine (13.8±9.0-fold increase, p = 0.0134). We found a synergistic upregulation of SP-B mRNA expression induced by co-administration of various glucocorticoids and caffeine, achieved by accumulation of intracellular cAMP. This effect was mediated by a caffeine-dependent phosphodiesterase inhibition and by upregulation of both ErbB4 and the GR. These results suggested that caffeine is able to induce the expression of SP-transcription factors and affects the signaling pathways of glucocorticoids, amplifying their effects. Co-administration of caffeine and corticosteroids may therefore be of benefit in surfactant homeostasis.